Supramolecular polymers fabricated by orthogonal self-assembly based on multiple hydrogen bonding and macrocyclic host–guest interactions - Xiao, Tangxin; Zhou, Ling; Sun, Xiao-Qiang; Huang, Feihe; Lin, Chen; Wang, Leyong (Chinese chemical letters, 2020)
Recent developments on supramolecular polymers fabricated by orthogonal self-assembly based on hydrogen bonding and host–guest interactions were summarized. Supramolecular polymers constructed by orthogonal self–assembly based on multiple hydrogen bonding and macrocyclic host–guest interactions have received increasing attention due to their elegant structures, outstanding properties, and potential applications. Hydrogen bonding endows these supramolecular polymers with good adaptability and reversibility, while macrocyclic host–guest interactions give them good selectivity and versatile stimuli-responsiveness. Therefore, functional supramolecular polymers fabricated by these two highly specific, noninterfering interactions in an orthogonal way have shown wide applications in the fields of molecular machines, electronics, soft materials, etc. In this review, we discuss the recent advances of functional supramolecular polymers fabricated by orthogonal self-assembly based on multiple hydrogen bonding and host–guest interactions. In particular, we focus on crown ether- and pillar[n]arene-based supramolecular polymers due to their compatibility with multiple hydrogen bonds in organic solution. The fabrication strategies, interesting properties, and potential applications of these advanced supramolecular materials are mainly concerned. [Display omitted]